Educational Program of Czech Nuclear Operator CEZ Group as a Part of Non-Formal Environmental Education - Yuliia Taratorkina (Pedagogical Discourse, 2017)
The article highlights the basic principles of the educational program developed and implemented by CEZ Group, the operator of nuclear power plants in the Czech Republic. Educational program ИWorld of Energy’ initiated in 1992 under the title ИEnergy for Everybody’ provides systematic and comprehensive information for young people and offers students, teachers as well as educational establishments help in understanding electric power and integrating related topics into school curricula. The main goal of the educational program is to shape one’s objective attitude to the environmental issues and to energy generation, in particular. Such approach deepens links between educational establishments and industrial groups and contributes to improving the quality of natural science teaching.The timeframe of program implementation and the main forms of educational activities are outlined in the article. It was ascertained that lectures, discussions, seminars and excursions are highly widespread within the framework of the educational program. Applied methods and principles are considered in the article.A wide range of educational materials has been analyzed. Educational program is implemented with the help of manuals, textbooks, brochures, educational complexes, tables and posters developed by specialists of CEZ Group. The content of educational films concerned with environmental issues is revealed. The films are grouped according to the topics and include electricity, energy generation , physics, nuclear energy, renewable sources of energy and fossil sources. The program includes educational films tackling methodological issues and designed for teachers. The means of education presented at the information centers of Temelin and Dukovany are described in the article. Main constructions and equipment of nuclear power plants are represented by interactive and dimensional models. Information and multimedia technologies are commonly used to improve understanding of nuclear physics.